ANALISIS POTENSI DAN REALISASI PENDAPATAN ASLI DAERAH DALAM MENCAPAI KEMANDIRIAN KEUANGAN DAERAH DI KABUPATEN SEKADAU TAHUN 2006-2011 - B61108042, SARNO (Jurnal Ekonomi Daerah (JEDA), 2013)
ABSTRACTThis research of The Regions OriginalRevenue Realization Potency inAchieving Region Finance Independence of Regency Sekadau Year 2006-2011. itaims to analyze regency region financial conditions of Seakdau Regency, how isgrowth, composition, effectiveness, self region acceptance liability, and PAD'Sacceptance elasticity at Sekadau Regency, as one of financial performanceindicator region, on year period that is utilized 2006 to 2011.The variable that analyzed is, all the regions revenues component, PAD,taxes, retribution, etc. propertied region, Population, and PDRB by use of dataskunder that acquired of on duty Regency Region Income sekadau and BPS(Sekadau's Regency in Numeral).Result observationaling to point out that up to growth research periodPAD Sekadau's Regency as big as 45.94 % by Region Taxes compositions 27%,Region Retribution 18%, Wealth management result region 7%, and etc. PAD is48%. While PAD'S acceptance effectiveness up to that period average as big as98.61%. Degrees arithmetic result Decentralize Fiscal at Regency sekadau thatbottommost, up to year period 2006-2011 which is average just as big as 2,73 %.this bottommost bases Depdagri's criterion.Elasticities arithmetic result point out PAD'S growth sekadau inelastis'sregency to PDRB namely as big as 0,35. Meanwhile elasticity to population as bigas 0,05(inelastis). Its mean is changed or added islandic as big as 1 % makechanging or added total PAD'S acceptances as big as 0,35%, and is changed oradded islandic as big as 1 % make changing or added total PAD'S acceptances asbig as 0,055%, .Key word: Effectiveness, Elasticity, PAD, Financially Region.